THE ROLE OF USING NEW TECHNIQUES AND METHODS TEACHING ENGLISH LANGUAGES - Narmuratov Zayniddin Radjabovich; Khayitmurodova Mokhira Abdikhofiz kizi (Лучшие интеллектуальные исследования, 2024)
Summary: People have used computer technology in various aspects for all his works. It is technology we need to use for everyday life. People have to get update date for performing in-tech industry. Shortly speaking, the industry we live in is driven by technology, and cannot be denied. Life methods we teach must be suitable for the level, degree of students, especially, ones who studies at technical faculties.